Accentuation of Nominal Words in the Vilnius Speech: de Saussure and Fortunatov’s synchronic law - Urbanavičienė, Jolita (Taikomoji kalbotyra, 2014)
The article presents the research on how Vilnians follow the main synchronic accentuation law of the Lithuanian language – de Saussure and Fortunatov’s (SF) synchronic law. The research aims at evaluation of whether the stress of nominal words is often not placed on attracting endings; whether accentuation tendencies of Vilnians are predetermined by external (social) factors – age, gender, education; what impact on the accentuation of townsmen is made by dialects. The empirical research material includes 30 direct interviews recorded from 18–75 year-old Vilnians (total number includes 26 hours of records). Sociolinguistic variables were coded via the language element analysis programme CLAN, statistical significance of the results was analysed through SPSS (ANOVA and t-tests). SF law was chosen as the axis of the research, which effect (accentuation of attractive endings) is to be linked with standard language accentuation system. Weakened SF law effect (the stress falls on stems preceding attractive endings) is to be linked with levelling of accents specific for eastern highlanders subdialects and accentuation system changes related with it: accentuation of column model, hypercorrection accentuation and accentuation variability. It was established that in view of accentuation the Vilnius speech is not homogenous. The divide separating most likely two individual phonological systems is between the older (over 50 years old) and two younger generations (18-29 years old and 30-49 years old). In the vertical of language variety, situated between dialect and standard language, older Vilnians language, formed and influenced mostly by eastern highlander’s subdialect, is closer to dialect, whilst middle and younger generation Vilnian’s speech is closer to standard language. In older generation of Vilnians speech 59 % of nominal words with attractive endings are accentuated in stems, whilst in two younger generations (Vilnians urbanolect) – vice versa: 58-63% attractive endings are accentuated by SF law. The research showed statistically significant influence of the age, gender, social status of the informants and activity developed by them on accentuation tendencies. More rare application of SF law is to be linked with the category of male gender, low social status and traditional activity (of industrial enterprises). More frequent application of SF law is to be linked with female gender, high social status and modern activity (of knowledge enterprises, service areas).
Keywords: Vilnius speech; sociolinguistic variable; accentuation of nominal words; de Saussure and Fortunatov’s synchronic law; standard language